Evaluation of the Selected Parameters of Inflammation in Patients with Haemorrhagic Stroke - Piotr Rajewski; Adam Wiśniewski; Magdalena Nowaczewska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. In the acute phase of stroke, the development of inflammation within the stroke focus can be observed. Therefore, in response to the inflammatory process in the brain, an inflammatory reaction occurs in the peripheral blood. Aim. The aim of the study was to assess the parameters of inflammation in peripheral blood in a group of patients with haemorrhagic stroke. Material and Methods. The study included 64 patients with haemorrhagic stroke hospitalized at the Stroke Centre of the Department of Neurology, University Hospital no. 1 in Bydgoszcz. The type and location of the stroke were verified by a head CT scan performed on the first day of hospitalization. On the first day of stroke, together with routine laboratory tests, the level of CRP1, WBC1, PCT, OB and fibrinogen1 was determined. CRP2, WBC2 and fibrinogen2 levels were repeated on the 14th day of stroke. Patients with infection were excluded from the study. Non-parametric statistical methods were used in the analysis: the Mann–Whitney test, the Kruskal–Wallis test and the Spearman correlation coefficient. Results. Subcortical localization of the haemorrhagic focus was found in the majority of patients. Both baseline and control CRP and WBC values were outside the laboratory range. There were no statistically significant differences between the baseline and control CRP and WBC values, while the control fibrinogen level was significantly higher than baseline (p<0.041). Patients who died and/or those with impaired consciousness had statistically significantly higher values of inflammatory parameters (except OB, PCT and FIBR1) compared to patients who survived and were conscious. Conclusions. In our study, we observed a significant increase in fibrinogen levels 14 days after the onset of the stroke. In addition, the control level of fibrinogen correlated with the size of the haemorrhagic focus and the clinical condition of the patients. Further research is needed in this area. (JNNN 2023;12(1):3–8)